2009
DOI: 10.1037/a0014387
|View full text |Cite
|
Sign up to set email alerts
|

Variations of emotional display rules within and across cultures: A comparison between Canada, USA, and Japan.

Abstract: This study investigates emotional display rules for seven basic emotions. The main goal was to compare emotional display rules of Canadians, US Americans, and Japanese across as well as within cultures regarding the specific emotion, the type of interaction partner, and gender. A total of 835 university students participated in the study. The results indicate that Japanese display rules permit the expression of powerful (anger, contempt, and disgust) significantly less than those of the two North American samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
191
2
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 251 publications
(225 citation statements)
references
References 33 publications
14
191
2
3
Order By: Relevance
“…Our finding supports the idea that positive and negative emotions are independent yet can co-exist in the sport context . In addition, it provides support for the notion that East Asians experience mixed emotions (Miyamoto et al, 2010) and are more likely to engage in dialectical thinking, believing that positive and negative feelings can be experienced concurrently (Safdar et al, 2009).…”
Section: Emotionsmentioning
confidence: 64%
See 1 more Smart Citation
“…Our finding supports the idea that positive and negative emotions are independent yet can co-exist in the sport context . In addition, it provides support for the notion that East Asians experience mixed emotions (Miyamoto et al, 2010) and are more likely to engage in dialectical thinking, believing that positive and negative feelings can be experienced concurrently (Safdar et al, 2009).…”
Section: Emotionsmentioning
confidence: 64%
“…While the physiological response associated with emotions appears to be invariant, the behavioural expression (facial in particular) varies across cultures (Tsai, Levenson, & Carstensen, 2000). East Asians, for example, are more likely to engage in dialectical thinking believing that positive and negative feelings co-exist (Safdar et al, 2009). Miyamoto, Uchida, and Ellsworth (2010) found that for a positive event (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In general, individualistic cultures promote primacy of individual needs, and individuals are encouraged to be authentic and open with their expression (Butler et al, 2007). Collectivist cultures value emotion suppression (Matsumoto et al, 2008), generally have more rules for expression management, and are more sensitive to others around them when expressing emotion, especially negative emotions (Butler et al, 2007;Safdar et al, 2009;Wei et al, 2013). Thus, extended to expression of positive and negative emotions we predict:…”
Section: The Singapore Contextmentioning
confidence: 96%
“…Each culture has specific rules, called display rules, which dictate what is appropriate to express (Diefendorff & Greguras, 2009;Fok et al, 2008;Saarni, 1979;Safdar et al, 2009). These rules consist of two subsets: normative masking and emotion dialects.…”
Section: Display Rules: Effect Of Cultural Norms On Customer Expressionmentioning
confidence: 99%
“…As a result of socialization, certain normative masking display rules are reinforced, which in turn shapes each person's view of the appropriateness of certain nonverbal behaviors (Brody & Fischer, 2000;Malatesta & Haviland, 1982;Mesquita, 2010). For example, Japanese display rules more strictly limit display of powerful emotions (anger, disgust, and contempt) than those in U.S. or Canadian cultures (Safdar et al, 2009). Although display rules in Eastern cultures tend to encourage masking true feelings, they also support the expression of politeness and social status deference through nonverbal behavior, which implies they may be more expressive in some contexts (Ambady et al, 1996).…”
Section: Normative Maskingmentioning
confidence: 99%